Effects of Nitrification Inhibitors on Mineral Nitrogen Dynamics in Agriculture Soils - Tindaon, Ferisman; Benckiser, Gero; Ottow, Johannes Carl Gottlieb (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Experiments were conducted under laboratory conditions to elucidate the effect of three nitrification inhibitors viz, 3.4dime-thylpyrazo-lephosphate (DMPP), 4-Chlormethylpyrazole (ClMP) and dicyandiamide (DCD) on mineral nitrogen dynamics of (NH4)2SO4 in soil incubated at 25oC in soils. The quantitative determination of ammonium, nitrite and nitrate were carried out spectrophotometrically, while potential denitrify-cation capacity (PDC) was measured gas chromatographically. DMPP, ClMP and DCD were used on recommended rates of 90kg N ha-1 corres-ponding to 0.36µg DMPP; 0.25µg ClMP and 10µg DCD g-1 dry soil. In all treatments, the influence of 1, 10, 50, 100, 250 and 500 times of the recommended-concentrations were examined. Results suggested that DMPP, ClMP and DCD applied at rates generally recommended for agricultural use may not be effective to inhibit nitrification. Thus even at the highest tested NIs-concentrations, nitrate and nitrite formation still occurred. Application of high concentrations of these chemicals up to 180µg DMPP, 125µg ClMP and 2500µg DCD were needed for inhibiting nitrification completely. The three NIs began to inhibit PDC at 10 to 50 times recommended concentration and were more effective in sandy than in loamy or clay soils. ClMP influenced PDC at much lower concentration as DMPP or DCD. Keywords: nitrification inhibitors, mineral nitrogen dynamics